State of art the competing risks survival analysis for cancer patients - Asghari Jafarabadi, Mohammad; Pourhosseingholi, Mohammad Amin; Hajizadeh, Ebrahim; Fatemi, Seyed Reza (Translational Gastrointestinal Cancer; Vol 3, No 4 (October 22, 2014): Translational Gastrointestinal Cancer (Biostatistics and Epidemiology Models in Gastrointestinal Cancers), 2014)
Background and Aim: In the competing risks problem, the cause-specific hazard rates are usually estimated by considering the independence assumption. However, this assumption may not be fulfilled in various practical situations. This paper addresses the problem of independence assumption in the competing risks survival analysis by including frailty component in the model. The finding was used to analyze the colorectal cancer patients’data. Methods: The Weibull distribution for competing risks including Gamma frailty was introduced and fitted on colorectal cancer data. The findings showed a substantial adjustment for model accuracy and precision by inserting frailty component, so that both the parameter estimates and their SE’s have been adjusted. Conclusions: The findings may be useful for situations at which the independence assumption of failure times is not satisfied such as competing risks and multicenter clinical trials.